2022
DOI: 10.1186/s12909-022-03449-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring culinary medicine as a promising method of nutritional education in medical school: a scoping review

Abstract: Background Dietary modifications are considered a first-line intervention for chronic disease management, yet graduating doctors still report not feeling competent to counsel patients on their diet. Research has focused on methods to address this shortfall in physician competency, including culinary medicine. Culinary medicine is an approach to education that involves hands-on food and cooking learning experiences to equip participants with tools for improving the nutrition behaviour and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…To better understand the adoption of and best practices for CM education in medical school, a group of subject matter experts reviewed two recent scoping reviews 15 , 25 to identify types of education and barriers and facilitators for implementation. Articles that were included in the scoping reviews were thematically coded and organized into emergent themes.…”
Section: Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the adoption of and best practices for CM education in medical school, a group of subject matter experts reviewed two recent scoping reviews 15 , 25 to identify types of education and barriers and facilitators for implementation. Articles that were included in the scoping reviews were thematically coded and organized into emergent themes.…”
Section: Bodymentioning
confidence: 99%
“…CM education is often offered as an elective recognized by an academic center and includes didactic learning through online or in-person lectures and hands-on culinary experiences. 15 , 25 Some electives also include case-based learning in groups and class assignments. Although funding information is limited, one scoping review suggests that most electives are funded through medical schools, the dean's office, philanthropy, or various grants.…”
Section: Electivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of such programs showed that there is marked heterogeneity in organization and curricula of such programs. 143 In addition, in the event that FIM interventions affect prescription needs, health professionals should be educated on modifying the use of medications in alignment with FIM interventions. Greater standardization of professional education in nutrition science and its relationship to health and health care use, FIM, and FIM research could lead to a larger and more highly specialized health care professional base, greater rigor in research, and increased likelihood of adoption of FIM in health care.…”
Section: Efforts Concurrent With Fim Researchmentioning
confidence: 99%
“…In 2022, 14 new publications evaluated the viability of using CMC in medical/nutritional education. 13,21,41,[50][51][52] Studies have also evaluated knowledge and confidence in counselling. 31,35 Based on the years of growth of the CM literature, we have identified three stages of literature development: Early stage (1992-2016), modest growth stage (2017-2019) and emerging stage (2020-2022).…”
Section: Country-wise Contributionmentioning
confidence: 99%